Dynamic Changes in Occupancy of Histone Variant H2A.Z during Induced Somatic Cell Reprogramming - Fulu Dong; Zhenwei Song; Jiali Yu; Baole Zhang; BaoChun Jiang; Ying Shen; Youde Lu; Chunlei Song; Peiqing Cong; Honglin Liu (Stem Cells International)
The development of induced pluripotent stem cells (iPSCs) has enabled study of the mechanisms underlying cellular reprogramming. Here, we have studied the dynamic distribution of H2A.Z during induced reprogramming with chromatin immunoprecipitation deep sequencing (ChIP-Seq). We found that H2A.Z tended to accumulate around transcription start site (TSS) and incorporate in genes with a high transcriptional activity. GO analysis with H2A.Z incorporated genes indicated that most genes are involved in chromatin assembly or disassembly and chromatin modification both in MEF and Day 7 samples, not in iPSCs. Furthermore, we detected the highest level of incorporation of H2A.Z around TSS in Day 7 samples compared to MEFs and iPSCs. GO analysis with only incorporated genes in Day 7 also displayed the function of chromatin remodeling. So, we speculate H2A.Z may be responsible for chromatin remodeling to enhance the access of transcription factors to genes important for pluripotency. This study therefore provides a deeper understanding of the mechanisms underlying induced reprogramming.